Retracted: A Novel Adaptive Terahertz System for Reliable and Efficient Maritime Communications Under Hostile Sea Conditions - Jianxin Feng; Jingjing Xu; Chengsheng Pan; Yuanming Ding; Hui Fang (IEEE Access)
Terahertz (THz) frequency band has been widely used in indoor, outdoor and space communications due to its advantage of large available bandwidth. However, limited research has been conducted to apply THz technique in maritime communications as hostile sea conditions cause significant path loss, thus leading to unacceptable signal error rate. In this paper, we propose a novel adaptive THz maritime communication system to tackle the above-mentioned challenge. Specifically, we design a joint source-channel coding scheme by using system random linear network coding (sRLNC) and Reed-Solomon (RS) to ensure transmission reliability. To further improve the transmission efficiency, we propose a novel triple-channel communication architecture facilitated by a very high frequency (VHF) feedback channel. With this design, the source data can be transmitted via the THz main channel while the coding redundancy is dispatched in the auxiliary channel. Meanwhile, the feedback channel allows sender to use an adaptive mechanism to achieve the transmission efficiency with higher transmission rate over long communication distance. In addition, we adopt the Doppler frequency offset in maritime environment to compensate both relative movement between communication parties and adversarial maritime factors, e.g., strong wind and extreme sea states. Simulation results demonstrate that our proposed THz system has remarkable capability not only to improve the communication efficiency up to 20Gbps compared to those conventional high frequency (HF), VHF and millimeter wave communication systems but also to transmit data over a longer distance with lower BERs.